Penanganan Siswa Berperilaku Agresif di SD Negeri Karangreja 2 Kutasari Purbalingga - Lutfi Imanan Dianto; Novan Ardy Wiyani; Mukti Amini (Jurnal Kependidikan, 2021)
This study was aimed at obtaining a description of how to deal with students' aggressive behavior at SDN 2 Karangreja, Kutasari sub-district, Puerbalingga district. This research is a case study research conducted with a qualitative approach. Data were collected using interview, observation, and documentation techniques. Then the data were analyzed through three stages of data analysis, namely data reduction, data display, and conclusion drawing. The results showed that the form of aggressive behavior carried out by students was verbal and nonverbal aggressiveness. The handling is done by reducing repressive actions on aggressive students, not giving physical punishment to aggressive students, paying attention and appreciation for positive aggressive student behavior, giving confidence to aggressive students, providing comfort to all students, and limiting student rights. Teachers have carried out optimal handling, however, parents are still lacking in providing treatment.